Synthesis and Characterization of Some Mixed Ligand Complexes of Zn(II) with 4, 4´- Bipyridine: Anti-inflammatory and Analgesic Activities of these Complexes - Hossain, M. A.; Alam, M. A.; Zahan, R.; Sheikh, C. M.; Islam, M. A. A. A. A. (Journal of Scientific Research, 2014)
<!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]--> The mixed ligand complexes of Zn(II) with 4,4-bipyridine and some organic acids or amino acids were prepared in the solid form and characterized by elemental analysis, conductivity, magnetic moment measurement, IR, 1H-NMR, 13C-NMR and FAB+ mass studies. To study anti-inflammatory and analgesic activities of these complexes, some Swiss albino mice of 5-7 weeks old were taken. One dose of the test compounds of 10 mg/kg was selected throughout the research work. The anti-inflammatory activity of the test compounds were determined by carrageenan induced mice paw edema inhibition method. The analgesic activity was determined by acetic acid induced writhing methods. These three compounds showed positive effects as anti-inflammatory and analgesic agents. Anti- inflammatory and analgesic activities of the test compounds at 50 mg/kg were quite comparable to those of standard drugs at 10 mg/kg. Keywords: Zinc; Organic acids; 4, 4'-Bipyridine; Anti-inflammatory; Analgesic activity. © 2014 JSR Publications. ISSN: 2070-0237 (Print); 2070-0245 (Online). All rights reserved. doi: http://dx.doi.org/10.3329/jsr.v6i2.16994 J. Sci. Res. 6 (2), 309-318 (2014) <!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin:0cm; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;} --> <!--[endif] --><!--[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin:0in; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Times New Roman";} > <! [endif] -->